Carbon emission disclosure and firm value of carbon-intensive firms - Saheed Issa; Abdulbaki Teniola Ubandawaki; Ayodele Akande; Abdulkadri Toyin Alabi (Journal of Perspectives in Management)
The expansion of global economic activities by firms has raised increasing concerns over unsustainable energy consumption, which is contributing to global carbon emissions and posing a significant threat to the planet's climate and environment. This has led to intensive growth in investor pressure for carbon emission mitigation and disclosure. The purpose of this study is to investigate the relationship between carbon disclosure and firm value as well as examining the moderating role of external assurance on both constructs. The data used were extracted from annual/stand-alone sustainability reports of carbon-intensive firms in Nigeria. Using Generalized Least Square regression analysis on 370 firm-year observations, this study finds that external assurance has a significant moderating role in increasing the effect of carbon disclosure on firm value. Carbon disclosure and external assurance also have a direct positive impact on firm value. The study recommends integrating carbon information into regulatory requirements and setting mandatory standards for sustainability assurance practices.